The Implementation of the Dewey Decimal Classification (DDC) System in Managing Library Administration - Fitrotin Azizah; Adi Wibowo; Akhmad Saiful Bakri (Al-Qalam Institue, 2026)
This study aims to analyze the implementation of the Dewey Decimal Classification (DDC) system in library administration management. The research focuses on how the DDC system is applied in classifying library collections, organizing materials, and improving the effectiveness of administrative services. A qualitative research method with a descriptive approach was employed. Data were collected through direct observation, in-depth interviews with librarians, and documentation analysis related to library administration activities. The results show that the implementation of the DDC system contributes significantly to more systematic and well-structured collection management. The use of DDC facilitates information retrieval for users, enhances the efficiency and accuracy of administrative processes, and supports librarians in managing collections in an orderly and consistent manner. Furthermore, the DDC system strengthens library governance by providing clear classification standards that improve service quality and administrative accountability. The findings of this study indicate that effective implementation of the DDC system can serve as a strategic instrument for improving library administration management and can be adopted by other educational institutions, particularly school and madrasah libraries, to support optimal learning resources and information services